Pharmacokinetics and Safety of Voriconazole Intravenous-to-Oral Switch Regimens in Immunocompromised Japanese Pediatric Patients - Mori, Masaaki (Antimicrob Agents Chemother, 2015)
The aim of this study was to investigate the pharmacokinetics, safety, and tolerability of voriconazole following intravenous-to-oral switch regimens used with immunocompromised Japanese pediatric subjects (age 2 to <15 years) at high risk for systemic fungal infection. Twenty-one patients received intravenous-to-oral switch regimens based on a recent population pharmacokinetic modeling; they were given 9 mg/kg of body weight followed by 8 mg/kg of intravenous (i.v.) voriconazole every 12 h (q12h), and 9 mg/kg (maximum, 350 mg) of oral voriconazole q12h (for patients age 2 to <12 or 12 to <15 years and <50 kg) or 6 mg/kg followed by 4 mg/kg of i.v. voriconazole q12h and 200 mg of oral voriconazole q12h (for patients age 12 to <15 years and ≥50 kg). The steady-state area under the curve over the 12-h dosing interval (AUC(0–12,ss)) was calculated using the noncompartmental method and compared with the predicted exposures in Western pediatric subjects based on the abovementioned modeling. The geometric mean (coefficient of variation) AUC(0–12,ss) values for the intravenous and oral regimens were 51.1 μg · h/ml (68%) and 45.8 μg · h/ml (90%), respectively; there was a high correlation between AUC(0–12,ss) and trough concentration. Although the average exposures were higher in the Japanese patients than those in the Western pediatric subjects, the overall voriconazole exposures were comparable between these two groups due to large interindividual variability. The exposures in the 2 cytochrome P450 2C19 poor metabolizers were among the highest. Voriconazole was well tolerated. The most common treatment-related adverse events were photophobia and abnormal hepatic function. These recommended doses derived from the modeling appear to be appropriate for Japanese pediatric patients, showing no additional safety risks compared to those with adult patients. (This study has been registered at ClinicalTrials.gov under registration no. NCT01383993.)